Perancangan Sistem Informasi Stok Barang di Gudang Toko Viola Berbasis Website - Muhamad Ali Kasri; Firman Firman; Rahda Putri Tahia; Ika Setianingsih (Universitas Pendidikan Muhammadiyah Sorong, 2023)
Viola shop is a wholesale and retail store in Salawati that offers a variety of products in the form of basic necessities, stationery, handyman equipment and so on. The purpose of this research is to design a website and a guidebook for the stock information system at the Viola Store Warehouse. The type of research used is research and development and the development model used is the prototype model. The trials used were blackbox trials and field trials. The subjects of this research are warehouse officers, shop owners, 3 students and 7 customers or the public. Based on the results of the research on designing a stock information system at the Viola Store Warehouse, the results of expert validation obtained very good conclusions, therefore researchers could conduct field trials to respondents. The results of field trials with the assessment of system quality aspects get an average of 3.6 percentages of 90% and get very good conclusions, navigation aspects get an average of 3.4 percentages of 84% and get very good conclusions, and aspects of user satisfaction get an average average 3.8 percentage 95% and get a very good conclusion. The ease of understanding the guidebook by the respondents got an average score of 3.8 and a percentage of 94% with a very good conclusion. The results of this study indicate that the design of an inventory information system at the Viola Store Warehouse based website and guidebook is feasible to use